Preclinical investigation for developing injectable fiducial markers using a mixture of BaSO4 and biodegradable polymer for proton therapy. Issue 5 (1st May 2015) - Ahn, Sang Hee; Gil, Moon Soo; Lee, Doo Sung; Han, Youngyih; Park, Hee Chul; Sohn, Jason W.; Kim, Hye Yeong; Shin, Eun Hyuk; Yu, Jeong Il; Noh, Jae Myoung; Cho, Jun Sang; Ahn, Sung Hwan; et al.
Abstract : Purpose: The aim of this study is to investigate the use of mixture of BaSO4 and biodegradable polymer as an injectable nonmetallic fiducial marker to reduce artifacts in x‐ray images, decrease the absorbed dose distortion in proton therapy, and replace permanent metal markers. Methods: Two samples were made with 90 wt. % polymer phosphate buffer saline (PBS) and 10 wt. % BaSO4 ( B 1) or 20 wt. % BaSO4 ( B 2). Two animal models (mice and rats) were used. To test the injectability and in vivo gelation, a volume of 200 μ l at a p H 5.8 were injected into the Sprague‐Dawley rats. After sacrificing the rats over time, the authors checked the gel morphology. Detectability of the markers in the x‐ray images was tested for two sizes (diameters of 1 and 2 mm) for B 1 and B 2. Four samples were injected into BALB/C mice. The polymer mixed with BaSO4 transform from SOL at 20 °C with a p H of 6.0 to GEL in the living body at 37 °C with a p H of 7.4, so the size of the fiducial marker could be controlled by adjusting the injected volume. The detectability of the BaSO4 marker was measured in x‐ray images of cone beam CT (CBCT), on‐board imager [anterior–posterior (AP), lateral], and fluoroscopy (AP, lateral) using a Novalis‐TX (Varian Medical Systems, Palo Alto, CA) repeatedly over 4 months. The volume, HU, and artifacts for the markers were measured in the CBCT images. Artifacts were compared to those of gold marker by analyzing the HU distribution. The dose distortion in proton therapy was computed by using a Monte Carlo (MC) code. A cylindrical shaped marker (diameter: 1 or 2 mm, length: 3 mm) made of gold, stainless‐steel [304], titanium, and 20 wt. % BaSO4 was positioned at the center of the spread‐out Bragg peak (SOBP) in parallel or perpendicular to the beam entrance. The dose distortion was measured on the depth dose profile across the markers. Results: Transformation to GEL and the biodegradation were verified. All BaSO4 markers could be detected in the CBCT. In the OBI and fluoroscopy images, all markers visible in the AP, but only B 2(2 mm) could be identified in the lateral images. Changes of BaSO4 position were not detected in vivo (mice). The volume of the markers decreased by up to 65% and the HU increased by 22%, on average. The mean HU values around the B 1, B 2, and gold markers were 121.30 [standard deviation (SD): 54.86], 126.31 (SD: 62.13), and 1070.7 (SD: 235.16), respectively. The MC‐simulated dose distortion for the BaSO4 markers was less than that of the commercially used markers. The dose reduction due to the gold marker was largest (15.05%) followed by stainless steel (7.92%) and titanium (6.92%). Dose reduction by B 2 (2 mm) was 4.75% and 0.53% in parallel and perpendicular orientations, respectively. Conclusions: BaSO4 mixed with PBS is a good contrast agent in biodegradable polymer marker because of minimal artifacts in x‐ray images and minimal dose reduction in proton therapy. The flexibility of the size is considered to be an advantage of this material over solid type fiducials.